Siak District, Riau Province Species and Density of Crabs in the Mangrove Ecosystem of the Rawa Mekar Jaya Village, Sungai Apit Sub-District - Nadya Wulan Sari; Eni Sumiarsih; M.Fauzi M.Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractRawa Mekar Jaya village is a mangrove conservation forest area. However anthropogenic activities conducted in that area damage the mangrove and thus negatively affects crabs living in that area. A research aims to identify crab species and its density was conducted in July 2019. There were 3 stations, with 3 plots/station and 5 sub plots/plot. In each sub plot, the crab were collected by hand. There were 5 crab species present, namely Periseserma sp, Uca vocans, Uca dussumieri, Uca rosea and Uca coarctata. The density of crab ranges from 5.8 - 15.6 organisms/m2. The water quality were as follows: temperature 28 – 29 °C; pH 6 -7; dissolved oxygen 4.18 - 5.04 mg/L and salinity 14 - 16‰. The correlation coefficient (r) of mangrove and crab densities was 0.951, indicates a positive correlation.Keyword: Periseserma sp, Rhizophora appiculata, mangrove forest ,Uca sp